Development status and trend prospect of computing power infrastructure - Wenjuan XING; Bo LEI; Qianying ZHAO (Dianxin kexue)
The development of digital technology drives the change and revolution of computing power infrastructure.The computing power infrastructure mainly referes to hardware and software infrastructure related to cloud computing, edge computing, end computing, as well as cutting-edge computing power infrastructure such as quantum computing.Firstly, the basic computing hardware and software facilities were discussed, and the development of data center towards diversification, intelligence, and greening was summarized.Secondly, the current technologies and development trends of cloud computing, edge computing and end computing were discussed.The form of the computing power infrastructure has developed from typical intensive cloud computing to multi-level, ubiquitous, converged cloud-edge-end computing.Finally, the current technologies and development of quantum computing were summarized, which was regarded as the key technologies of the next generation information revolution, with a view to provide reference for the research and development of computing power infrastructure.